The role of interferon signaling in neurodegeneration and neuropsychiatric disorders - Sirkis, Daniel W.; Oddi, Alexis P.; Jonson, Caroline; Bonham, Luke W.; Hoang, Phuong T.; Yokoyama, Jennifer S. (Frontiers in Psychiatry, 2024)
Recent advances in transcriptomics research have uncovered heightened interferon (IFN) responses in neurodegenerative diseases including Alzheimer’s disease, primary tauopathy, Parkinson’s disease, TDP-43 proteinopathy, and related mouse models. Augmented IFN signaling is now relatively well established for microglia in these contexts, but emerging work has highlighted a novel role for IFN-responsive T cells in the brain and peripheral blood in some types of neurodegeneration. These findings complement a body of literature implicating dysregulated IFN signaling in neuropsychiatric disorders including major depression and post-traumatic stress disorder. In this review, we will characterize and integrate advances in our understanding of IFN responses in neurodegenerative and neuropsychiatric disease, discuss how sex and ancestry modulate the IFN response, and examine potential mechanistic explanations for the upregulation of antiviral-like IFN signaling pathways in these seemingly non-viral neurological and psychiatric disorders.